Overwhelmed : literature, aesthetics, and the nineteenth-century information revolution - Lee, Maurice S. (Princeton University Press, 2019)
This book looks at how debates over the fate of literature in our digital age are powerfully conditioned by the nineteenth century's information revolution. It explains what happens to literature during an information revolution, and how readers and writers adapt to proliferating data and texts, both today and in the nineteenth century. Explores four key areas-reading, searching, counting, and testing-and analyzes diverse writings, from canonical works to lesser-known texts.